PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR PEMAHAMAN KONSEP DAN KEMAMPUAN MENGANALISIS GURU FISIKA SEKOLAH MENENGAH KEJURUAN (SMK) - Slamet Mugiono; Agus Setiawan (Universitas Sebelas Maret, 2014)
This paper presents the results of the development of understanding physics concepts test instruments and test the ability to analyze the physics teacher and vocational development of instruments that will be used in a web-assisted physics training (e-training) for vocational school physics teacher. The method used is a theoretical study, expert validation, and testing and analysis of the grain problem understanding the concept and the ability to analyze. The results are described in the narrative. The results obtained indicate that the steps in developing the instrument are: conduct training needs analysis, structuring and guide training programs, developing web-based teaching materials and teacher worksheets (LKG), develop the grain problem understanding the concept and the ability to analyze, develop observation, interview guides, questionnaires and training implementation. Once reviewed by an expert, test instruments further tested in the field in order to obtain points which meet the requirements. Tests performed on 25 SMK physics teachers in Bandung city, Cimahi and Bandung regency. Based on the results of the expert validation and test of 31 items was understanding the concept (PK) obtained 25 test items are fit for use. As for the ability to analyze test items (KM) of the 30 items onthe results obtained by 24 test items are fit for use Keywords: instruments, concepts understanding, ability analyzing